Chemical and phase inhomogeneity in LaNiO3 electrodes prepared by chemical solution deposition. Issue 1 (4th April 2021) - Atanova, A. V.; Zhigalina, O. M.; Khmelenin, D. N.; Kotova, N. M.; Seregin, D. S.; Vorotilov, K. A.
Abstract: The structure of lanthanum nickelate (LNO) thin film electrodes prepared by chemical solution deposition has been investigated. Features of LNO microstructure have been studied using high-resolution transmission electron microscopy techniques, electron diffraction, and elemental mapping by energy dispersive X-ray analysis. Structure evolution of LNO after crystallization in the temperature range of 550 ÷ 800 °C has been visualized. Chemical and phase delamination within each sublayer was revealed in the LNO structure over the entire temperature range. Nanograins of Ni3 O4 (С2/m), La2 O3 (С2/m), LaNiO3 ( P m 3 ¯ m ), and La2 Ni2 O5 (С2/m) phases were identified in the annealed LNO layer.